Wolf's isotopic response: Report of a case and review of literature - Rahul Mahajan; Dipankar De; Uma Nahar Saikia (Wolters Kluwer Medknow Publications, 2014)
"Wolf's isotopic response" refers to the occurrence of a new dermatosis at the site of previously healed dermatosis. A number of factors including viral, neural, vascular, and immunologic factors have been implicated in the causation of this peculiar response but none has been proven conclusively. Here, we report a case where lichen planus developed at the site of dermatofibrosarcoma protruberans that had been previously treated with surgery and radiotherapy. We also put forth a hypothesis on the genesis of isotopic response considering the above mentioned factors.